Matter distribution for power spectra with broken scale invariance - Amendola, Luca (Arxiv, 1994)
To test the primordial power spectra predicted by a double inflationary model with a break of amplitude $Δ=3$ at a scale of $2π/k≈ 10 \hm$ and CDM as dominant matter content, we perform PM simulations with 128$^3$ particles on a 256$^3$ grid. The broken scale invariance of the power spectra explains the extra power observed in the large-scale matter distribution. COBE-normalized spectra and a linear biasing with